Description of Pharmaceutical Discussion Using Group Discussion Method Among "Kantor Pusat" Members at Kadiri University Cafeteria - Prasetyawan, Fendy; Wahab, Charliandri Saputra; Dhafin, Anis Akhwan; Raharjo, Susilo Margining; Shutiawan, Muhammad Alviyan; Rianto, Sugeng (International Journal of Contemporary Sciences (IJCS), 2023)
Effective communication and pharmaceutical discussions at Kadiri University's Central Office are crucial in the current era of pharmaceutical advancements. The research focuses on exploring how group discussions enhance pharmaceutical understanding and collaboration, contributing to broader pharmaceutical science development. The methodology involves participatory observation, interviews, and document analysis to gain a comprehensive understanding of group discussion effectiveness. Philosophical discussions constitute 46% of central office discussions at Kadiri University, reflecting a significant emphasis on philosophical aspects in pharmaceutical talks. Pharmacy topics, at 35%, demonstrate a strong focus on core research areas. Political discussions, comprising 11%, indicate awareness of political implications in pharmacy management within the university. Ethics and Morality discussions, at 8%, suggest a lower focus but still acknowledge ethical dimensions in pharmaceutical discourse